IMPLEMENTATION OF INQUIRY-BASED WORKSHEETS ON ICE CREAM STABILITY TOPIC USING PROTECTIVE COLLOID - Fahmi Muhammad Nurdiansyah; Ferli Septi Irwansyah; Ida Farida (Gunung Djati Conference Series, 2021)
This study aimed to apply inquiry-based worksheets, to analyze the ability of inquiry skills starting from the stage of designing experiments, conducting experiments, and analyzing experimental data on the topic of ice cream stability using protective colloid. Worksheets were applied using a one shoot case study, a study conducted without a comparison class that aims to improve students' inquiry abilities. This research was conducted on fifteen students of fifth semester. The instruments used were descriptions of learning, inquiry-based worksheets, observation sheets, assessment sheets (performance and worksheets). The results of applying the worksheet showed the ability of students in designing experiments, conducting experiments, and analyzing experimental data obtained an average score of 90.75 which categorized very good. The ability to design experiments, conduct experiments, and analyze experimental data obtained results respectively 81.65 (very good); 93.75 (very good); and 96.87 (very good). Inquiry-based worksheets in this study can be used in the study of Food Chemistry, especially in food additives.